Solid oxide battery and manufacturing method thereof
By using alloy oxide particles of nickel and heterogeneous metals in the fuel electrode of solid oxide batteries, the shrinkage of nickel and the uniformity of their distribution is delayed, and the structural damage caused by nickel expansion and contraction is solved, and higher battery performance and durability are achieved.
Patent Information
- Application Number
- CN202380055386.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-19
- Filing Date
- 2023-11-10
- Publication Date
- 2025-03-25
AI Technical Summary
In solid oxide batteries, nickel expands and contracts at high temperatures and causes structural damage, affecting the durability of the battery.
By retarding the shrinkage of nickel during firing of the fuel electrode, alloying with nickel using heterogeneous metals such as tin, indium, bismuth or gallium to form alloy oxide particles, which are mainly distributed in the surface area of the alloy oxide particles of nickel.
The delayed shrinkage of nickel makes it widely distributed in the fuel electrode without aggregation, which increases the density of the three-phase boundary, improves the battery performance, and improves the durability of the battery by preventing the aggregation and deterioration of nickel.
Smart Images

Figure CN119698702A_ABST
Abstract
Description
Technical Field
[0001] This application claims priority to and the benefit of Korean Patent Application No. 10-2022-0159244 filed in the Korean Intellectual Property Office on November 24, 2022, and Korean Patent Application No. 10-2023-0051468 filed in the Korean Intellectual Property Office on April 19, 2023, the entire contents of which are incorporated herein by reference.
[0002] The present disclosure relates to a solid oxide battery and a method for manufacturing the same. Background Art
[0003] The solid oxide cell (SOC) is, for example, a solid oxide fuel cell (SOFC) or a solid oxide electrolyzer (SOEC), and generates electrical energy through the electrochemical reaction of the cell (which utilizes an air electrode, a fuel electrode, and a solid oxide electrolyte with oxygen ion conductivity) or electrolyzes water and generates hydrogen through the reverse reaction of the solid oxide fuel cell.
[0004] The solid oxide cell has a configuration in which an air electrode and a fuel electrode are disposed on both sides of a solid oxide electrolyte having oxygen ion conductivity to supply air and hydrogen to the air electrode and the fuel electrode respectively through flow paths formed in a separator, thereby generating electricity or performing electrolysis by an electrochemical reaction.
[0005] Solid oxide cells operate at high temperatures of 800°C or higher. Therefore, unlike polymer electrolyte fuel cells (low temperature fuel cells) that use highly active but expensive catalysts such as platinum, solid oxide cells have high activity and can therefore use inexpensive catalysts such as nickel. The better the performance of the fuel electrode, the higher the density of the three-phase boundary (TPB) where nickel, solid oxide and gas intersect, which is enhanced by uniformly and widely diffusing nickel within the solid oxide after firing.
[0006] However, when nickel, which constitutes about 40% of the volume of the fuel electrode, meets and aggregates with each other under high-temperature operating conditions and is exposed to oxidation and reduction processes due to repeated stopping and restarting, nickel may expand and shrink, resulting in the destruction of the entire structure of the solid oxide cell. Summary of the invention
[0007] Technical issues
[0008] In accordance with a solid oxide cell according to one aspect, by delaying the shrinkage of nickel (Ni) during the firing of the fuel electrode, nickel (Ni) is widely distributed without aggregation, the density of the three-phase boundary is increased to improve performance, and by preventing degradation during operation of the fuel electrode, durability can be improved.
[0009] Technical Solution
[0010] A solid oxide cell according to one aspect includes: a solid oxide electrolyte; and a fuel electrode and an air electrode, the fuel electrode being disposed on one side of the solid oxide electrolyte, and the air electrode being disposed on the other side of the solid oxide electrolyte. The fuel electrode includes alloy oxide particles of nickel (Ni) and a heterogeneous metal and a solid oxide electrolyte material, the heterogeneous metal being alloyable with nickel (Ni).
[0011] When the atomic percentage (at%) of the heterogeneous metal in the central region of the alloy oxide particle relative to all atoms is M core , and the atomic percentage (at%) of the heterogeneous metal in the surface region of the alloy particle relative to all atoms is M surface When 10×M core <M surface .
[0012] M core It may be the atomic percentage (at %) of the heterogeneous metal measured within the central region centered at the center of the alloy oxide particle and having a size of 10 nm×10 nm.
[0013] M surface It may be the atomic percentage (at %) of the heterogeneous metal measured within the surface region centered at an inner point within 20 nm from the surface of the alloy oxide particle toward the center and having a size of 2 nm×2 nm.
[0014] In the central region of the alloy oxide particle, the heterogeneous metal may be included in an amount of greater than or equal to 0.01 at % and less than 1 at % based on the total number of atoms.
[0015] The heterogeneous metal may be included in the surface region of the alloy oxide particle in an amount of greater than or equal to 0.1 at % and less than 10 at % based on the total number of atoms.
[0016] The heterogeneous metal may include tin (Sn), indium (In), bismuth (Bi), gallium (Ga), or a combination thereof.
[0017] The solid oxide electrolyte material may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
[0018] The solid oxide electrolyte may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
[0019] The air electrode may include lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), samarium strontium cobalt oxide (SSC), barium strontium cobalt iron oxide (BSCF), bismuth ruthenium oxide, or a combination thereof.
[0020] The solid oxide cell may be a solid oxide fuel cell (SOFC), a solid oxide electrolyzer (SOEC), or both.
[0021] According to another aspect, a method of manufacturing a solid oxide cell includes: coating a surface of nickel oxide (NiO) particles with a heterogeneous metal alloyable therewith; and forming a fuel electrode using a composition for forming a fuel electrode including the nickel oxide particles coated with the heterogeneous metal.
[0022] The heterogeneous metal may be coated on the surface of the nickel oxide (NiO) particle using a sputtering method, an atomic layer deposition (ALD) method, a physical vapor deposition (PVD) method, or a chemical vapor deposition (CVD) method.
[0023] The composition for forming the fuel electrode may further include a solid oxide electrolyte material.
[0024] The step of forming the fuel electrode may include casting and firing the composition for forming the fuel electrode.
[0025] A solid oxide cell according to one aspect includes: a solid oxide electrolyte; and a fuel electrode and an air electrode, the fuel electrode being disposed on one side of the solid oxide electrolyte, and the air electrode being disposed on the other side of the solid oxide electrolyte. The fuel electrode includes a solid oxide electrolyte material and alloy oxide particles of nickel (Ni) and a heterogeneous metal, the heterogeneous metal being alloyable with nickel (Ni), and the heterogeneous metal being mainly disposed in the surface region of the alloy oxide particles of nickel (Ni). The heterogeneous metal includes tin (Sn), indium (In), bismuth (Bi), gallium (Ga), or a combination thereof.
[0026] The surface region of the alloy oxide particle of nickel (Ni) may be a region centered at an inner point within 20 nm from the surface of the alloy oxide particle of nickel (Ni) toward the center and having a size of 2 nm×2 nm.
[0027] The atomic percentage of the heterogeneous metal relative to all atoms in the surface region of the alloy oxide particle may be 19 times or more the atomic percentage of the heterogeneous metal relative to all atoms at the central region of the alloy oxide particle.
[0028] Advantageous Effects of the Invention
[0029] In accordance with a solid oxide cell according to one aspect, by delaying the shrinkage of nickel (Ni) during the firing of the fuel electrode, nickel (Ni) is widely distributed without aggregation, the density of the three-phase boundary is increased to improve performance, and by preventing degradation during operation of the fuel electrode, durability can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is a diagram schematically illustrating a cross section of a solid oxide cell according to one aspect.
[0031] Figure 2 is a schematic diagram showing a solid oxide fuel cell according to a modified embodiment of an aspect.
[0032] Figure 3 is a schematic diagram showing a solid oxide electrolysis cell according to another variant embodiment of the one aspect.
[0033] Figure 4 It is the HAADF phase of the alloy oxide particles.
[0034] Figure 5 This is the EDS mapping result of nickel (Ni).
[0035] Figure 6 This is the EDS mapping result of tin (Sn).
[0036] Figure 7 is a scanning electron microscope (SEM) photograph of the fuel electrode in the solid oxide cell manufactured in Example 1.
[0037] Figure 8 is a scanning electron microscope (SEM) photograph of the fuel electrode in the solid oxide cell manufactured in Comparative Example 1.
[0038] Fig. 9 It shows the measurement Figure 7 The size distribution of the alloy oxide particles and Figure 8 A graph of the results of the size distribution of nickel oxide particles.
[0039] Fig.10 is a graph showing the results of measuring the accelerated durability of the solid oxide batteries prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION
[0040] Hereinafter, the present invention will be described in detail with reference to the accompanying drawings so that a person of ordinary skill in the art can practice. The drawings and descriptions are considered to be illustrative rather than restrictive in nature. Throughout the specification, the same reference numerals represent the same elements. In addition, the drawings are provided only to make the disclosed embodiments in this specification easy to understand, and are not to be construed as limiting the spirit disclosed in this specification, and it should be understood that the present invention includes all variations, equivalents and alternatives without departing from the scope and spirit of the present invention. In addition, some components are exaggerated, omitted or schematically depicted in the drawings, and the size of each component does not necessarily represent the actual size.
[0041] In addition, unless explicitly described to the contrary, the word “comprise” and variations such as “including” or “having”, will be understood to imply the inclusion of stated elements but not the exclusion of any other elements.
[0042] Figure 1 is a diagram schematically illustrating a cross section of a solid oxide cell 100 according to one aspect.
[0043] Reference Figure 1 , the solid oxide cell 100 includes: a solid oxide electrolyte 130 ; a fuel electrode 110 disposed on one side of the solid oxide electrolyte 130 ; and an air electrode 120 disposed on the other side of the solid oxide electrolyte 130 .
[0044] The fuel electrode 110 is used to electrochemically oxidize the fuel and transfer charges.
[0045] The fuel electrode 110 includes alloy oxide particles 111 of nickel (Ni) and a heterogeneous metal, and a solid oxide electrolyte material 112 , the heterogeneous metal being alloyable with the nickel (Ni).
[0046] The higher the density of the three-phase boundary (TPB) where nickel, solid oxide electrolyte material 112 and gas meet, the better the performance of the fuel electrode 110, which means that it is beneficial for nickel to diffuse uniformly and widely within the solid oxide electrolyte material 112 after firing.
[0047] However, when nickel, which constitutes approximately 40% of the volume of the fuel electrode 110, meets and aggregates with each other under high temperature operating conditions and is exposed to oxidation and reduction processes due to repeated stopping and restarting, the nickel may expand and contract, resulting in destruction of the entire structure of the solid oxide cell 100.
[0048] In the solid oxide cell 100 according to one aspect, when the atomic percentage (at%) of the heterogeneous metal in the central region of the alloy oxide particle relative to the total atoms is M core , and the atomic percentage (at%) of the heterogeneous metal in the surface region of the alloy particle relative to all atoms is M surface When 10×M core <M surface , the fuel electrode 110 includes nickel (Ni) and an alloy oxide particle 111 of a heterogeneous metal and satisfies 10×M core <M surface .
[0049] Here, the solid oxide cell 100 may have a first direction along which the fuel electrode 110, the solid oxide electrolyte 130 and the air electrode 120 are stacked, and a second direction and a third direction that are perpendicular to the first direction and also perpendicular to each other, wherein the at% of specific atoms in the central region or the surface region of the alloy oxide particle 111 relative to all atoms can be analyzed by analyzing a reflected electron image of a cross-section of the solid oxide cell 100 (a cross-section of the solid oxide cell 100 in the first direction and the third direction perpendicular to the second direction cut at the center of the second direction) using a scanning electron microscope (SEM) or observing a HAADF image of the cross-section using a scanning transmission electron microscope (STEM) or the like.
[0050] For example, the at% of a specific atom according to the position of the alloy oxide particle 111 can be measured by performing a composition analysis in a reflection electron image of a SEM or a HAADF image of a STEM by using an electron beam microanalyzer (EPMA). The composition analysis can be performed by obtaining measurement values at at least 3, at least 5, or at least 10 or more positions and calculating the average value of the measurement values to calculate the composition. When an electron beam microanalyzer (EPMA) is used to perform composition analysis, etc., EDS (energy dispersive spectrometer), WDS (wavelength dispersive spectrometer), etc. can be used as an X-ray spectrometer.
[0051] Alternatively, when analyzing the alloy oxide particles 111 using a reflected electron image of a SEM or a HAADF image of a STEM, nickel and a heterogeneous metal having a metallic bond can be identified as a portion with a bright contrast, and a non-metal component such as oxygen can be identified as a portion with a dark contrast. Therefore, the at% of a specific atom according to the position of the alloy oxide particle 111 can be calculated as an area ratio of the portion with a bright contrast to the entire measurement field of view by binarizing a cross-sectional image or the like. In addition, at least 3, at least 5, or at least 10 or more alloy oxide particles 111 are measured, and their measured values are calculated as an average value.
[0052] Here, the center of the alloy oxide particle 111 may be determined as a point where the maximum major axis of the alloy oxide particle 111 intersects with the maximum minor axis among the minor axes perpendicular to the maximum major axis, and the surface of the alloy oxide particle 111 may be determined as one of the points where the outermost side of the alloy oxide particle 111 intersects with the maximum major axis.
[0053] When the alloy oxide particles 111 satisfy 10×M core <M surface That is, when the surface of the alloy oxide particle 111 includes a region having a high content of heterogeneous metal, Ni is not aggregated due to delayed shrinkage of nickel (Ni), but is widely distributed during the firing of the fuel electrode 110. As a result, the density of the three-phase boundary of the fuel electrode 110 can be increased. In addition, the nickel alloy coated with the region having a high content of heterogeneous metal can prevent degradation due to aggregation of nickel during operation of the solid oxide cell 100, thereby improving durability.
[0054] For example, when the atomic percentage (at%) of the heterogeneous metal in the central region of the alloy oxide particle 111 relative to all atoms is M core , and the atomic percentage (at%) of the heterogeneous metal in the surface region of the alloy particle 111 relative to all atoms is M surface When 10×M core <M surface .
[0055] The surface region having a high content of heterogeneous metal is located near the outermost surface of the alloy oxide particle 111 and satisfies 10×M core <M surface .
[0056] Here, M core It may be at% of the heterogeneous metal measured in a central region centered at the center of the alloy oxide particle 111 and having a size of 10 nm×10 nm.
[0057] M surface It may be at% of the heterogeneous metal measured in a surface region centered at any inner point within 20 nm from the surface toward the center of the alloy oxide particle 111 and having a size of 2 nm×2 nm. For example, M surface It may be the at% of the heterogeneous metal measured within a surface region centered at an arbitrary interior point 20 nm away and having dimensions of 2 nm x 2 nm.
[0058] For example, the heterogeneous metal may be included in an amount of 0.01 at% or more and less than 1 at% based on all atoms in the central region of the alloy oxide particle 111. When the content of the heterogeneous metal is 1 at% or more in the central region of the alloy oxide particle 111, the resistance may increase, deteriorating the performance, but when the content of the heterogeneous metal is less than 0.01 at%, the influence of the heterogeneous metal may not be significant.
[0059] In addition, in the surface region of the alloy oxide particle 111, a heterogeneous metal may be included in an amount of 0.1 at% or more and less than 10 at% based on all atoms. Herein, in the surface region of the alloy oxide particle 111, at% of the heterogeneous metal is measured within a surface region centered at any inner point within 20 nm toward the center from the surface of the alloy oxide particle 111 and having a size of 2 nm×2 nm.
[0060] The heterogeneous metal is not particularly limited as long as it can be reduced and can form an alloy with nickel, but it is more desirable if it is a metal that can be more distributed in the surface area of the particles after alloying. For example, the heterogeneous metal may include tin (Sn), indium (In), bismuth (Bi), gallium (Ga), or a combination thereof.
[0061] The alloy oxide particles 111 may include a region having a high heterogeneous metal content in a surface region, thereby delaying shrinkage of nickel (Ni) during firing of the fuel electrode 110 and preventing aggregation.
[0062] The solid oxide electrolyte material 112 should have high oxygen ion conductivity and low electronic conductivity.
[0063] For example, the solid oxide electrolyte material 112 may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
[0064] In this case, the fuel electrode 110 may include a cermet in which alloy oxide particles 111 and a solid oxide electrolyte material 112 are combined. For example, when the alloy oxide particles 111 include an alloy of nickel (Ni) and tin (Sn) and the solid oxide electrolyte material 112 is yttria-stabilized zirconia (YSZ), the fuel electrode 110 includes a Ni-Sn / YSZ cermet.
[0065] For example, the thickness of the fuel electrode 110 may be, for example, 1 μm to 1000 μm or 5 μm to 100 μm.
[0066] The air electrode 120 includes an air electrode material. The air electrode material may be a material that reduces oxygen to oxygen ions.
[0067] For example, the air electrode material may include metal oxide particles having a perovskite crystal structure. Perovskite metal oxides are mixed ionic electronic conductor (MIEC) materials having both ionic conductivity and electronic conductivity, and have high oxygen diffusion coefficients and charge exchange reaction rate coefficients, so that redox reactions occur over the entire surface of the electrode, not just at the three-phase boundary.
[0068] The perovskite type metal oxide may be represented by Chemical Formula 1.
[0069] [Chemical formula 1]
[0070] ABO 3±γ
[0071] In Chemical Formula 1, A is an element including La, Ba, Sr, Sm, Gd, Ca, or a combination thereof, B is an element including Mn, Fe, Co, Ni, Cu, Ti, Nb, Cr, Sc, or a combination thereof, and γ represents oxygen excess or oxygen deficiency. For example, γ may be in the range of 0≤γ≤0.3.
[0072] For example, the perovskite type metal oxide may be represented by Chemical Formula 2.
[0073] [Chemical formula 2]
[0074] A' 1-x A” x B'O 3±γ
[0075] In Chemical Formula 2, A′ is an element including Ba, La, Sm or a combination thereof, A″ is an element including Sr, Ca, Ba or a combination thereof and is different from A′, B′ is an element including Mn, Fe, Co, Ni, Cu, Ti, Nb, Cr, Sc or a combination thereof, 0≤x<1, and γ represents oxygen excess or oxygen deficiency.
[0076] For example, the air electrode material may include lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), samarium strontium cobalt oxide (SSC), barium strontium cobalt iron oxide (BSCF), bismuth ruthenium oxide, or combinations thereof.
[0077] The air electrode may also include a solid oxide electrolyte material.
[0078] For example, the solid oxide electrolyte material may include yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
[0079] In this case, when the solid oxide electrolyte material is yttria-stabilized zirconia (YSZ) and the air electrode material is lanthanum strontium manganese oxide (LSM), the porous solid oxide composite may be a LSM-YSZ composite.
[0080] For example, the air electrode 120 may have a thickness of about 1 μm to about 100 μm or about 5 μm to about 50 μm.
[0081] The solid oxide electrolyte 130 plays a role in transporting the generated oxygen ions from the air electrode 120 to the fuel electrode 110 through ion conduction. The solid oxide electrolyte 130 may have air impermeability to prevent contact between air and the fuel electrode 110, and also prevents electrons generated at the fuel electrode 110 from moving directly toward the air electrode 120 due to high oxygen ion conductivity and low electron conductivity (high resistance, high insulation).
[0082] In addition, since the solid oxide electrolyte 130 has the air electrode 120 and the fuel electrode 110 on both sides thereof, which have a very large oxygen partial pressure difference, the aforementioned properties may need to be maintained in a wide oxygen partial pressure region.
[0083] The materials of these solid oxide electrolytes 130 are not particularly limited as long as they are generally used in the art, and may include, for example, yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
[0084] For example, the thickness of the solid oxide electrolyte 130 may be 10 nm to 100 μm or 100 nm to 50 μm.
[0085] Optionally, the solid oxide cell 100 may further include a current collecting layer (not shown) including an electrical conductor located on at least one side of the air electrode 120 (e.g., the outside of the air electrode 120). The current collecting layer may serve as a current collector to collect electricity in the configuration of the air electrode 120.
[0086] The collector layer may include, for example, lanthanum cobalt oxide (LaCoO3), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), lanthanum strontium cobalt manganese oxide (LSCM), lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), or a combination thereof. The collector layer may use the materials listed above alone or in a combination of two or more, wherein these materials may be formed into a single layer or two or more layers having a stacked structure.
[0087] The solid oxide cell 100 may be applied to various structures, such as a cylindrical (tubular) stack, a flat tubular stack, a planar stack, and the like.
[0088] In addition, the solid oxide cell 100 may be in the form of a unit cell stack. For example, a unit cell (membrane electrode assembly (MEA)) composed of an air electrode 120, a fuel electrode 110, and a solid oxide electrolyte 130 is stacked in series, and an electrically connected separator is provided between the unit cells to obtain a unit cell stack.
[0089] For example, the solid oxide cell may be a solid oxide fuel cell (SOFC), a solid oxide electrolyzer (SOEC), or both.
[0090] Figure 2 is a schematic diagram showing a case in which the solid oxide cell 100 is a solid oxide fuel cell.
[0091] Reference Figure 2 The solid oxide fuel cell 200 includes: a fuel electrode 210; an air electrode 220 facing the fuel electrode 210; and an oxygen ion conductive solid oxide electrolyte 230 located between the fuel electrode 210 and the air electrode 220.
[0092] As shown in Reaction Formula 1, the electrochemical reaction of the solid oxide fuel cell 200 includes: oxygen O2 at the air electrode 220 is converted into oxygen ions O2 - An air electrode reaction and a fuel electrode reaction in which the fuel (H2 or hydrocarbon) of the fuel electrode 210 reacts with the oxygen ions that have passed through the electrolyte.
[0093] [Reaction formula 1]
[0094] Air electrode reaction: 1 / 2O2+2e - →O2 -
[0095] Fuel electrode reaction: H2+O2 - →H2O+2e -
[0096] In the air electrode 220 of the solid oxide fuel cell 200, oxygen adsorbed into the electrode surface is dispersed and moves through surface diffusion to the three-phase boundary (three-phase boundary) where the solid oxide electrolyte 230, the air electrode 220 and the pores (not shown) intersect to obtain electrons to become oxygen ions, and the generated oxygen ions move toward the fuel electrode 210 through the solid oxide electrolyte 230.
[0097] In the fuel electrode 210 of the solid oxide fuel cell 200, the moving oxygen ions combine with the hydrogen contained in the fuel to generate water. At this time, the hydrogen releases electrons to become hydrogen ions (H + ) combines with oxygen ions. The released electrons move to the air electrode 220 through a wire (not shown) and change oxygen into oxygen ions. Through this movement of electrons, the solid oxide fuel cell 200 can perform a battery function.
[0098] Figure 3 is a schematic diagram showing a case where the solid oxide cell 100 is a solid oxide electrolysis cell.
[0099] Reference Figure 3 The solid oxide electrolysis cell 300 includes: an air electrode 310; a fuel electrode 320 disposed facing the air electrode 310; and an oxygen ion conductive solid oxide electrolyte 330 disposed between the air electrode 310 and the fuel electrode 320.
[0100] As shown in Reaction Formula 2, the electrochemical reaction of the solid oxide electrolysis cell 300 includes converting water (H2O) of the fuel electrode 320 into hydrogen (H2) and oxygen ions (O2 - ) and an air electrode reaction in which oxygen ions passing through the solid oxide electrolyte 330 are converted into oxygen (O2). This reaction is opposite to the reaction principle of a conventional fuel cell.
[0101] [Reaction 2]
[0102] Fuel electrode reaction: H2O+2e - →O2 - +H2
[0103] Air electrode reaction: O2 - →1 / 2O2+2e -
[0104] When power is applied to the solid oxide electrolysis cell 300 from the external power supply 340, the solid oxide electrolysis cell 300 is supplied with electrons from the external power supply 340. The electrons react with the water supplied to the fuel electrode 320 to generate hydrogen and oxygen ions. The hydrogen is released to the outside, and the oxygen ions pass through the electrolyte 330 to reach the air electrode 310. The oxygen ions moved to the air electrode 310 lose electrons and then become oxygen and are released to the outside. The electrons flow to the external power supply 340. Through this electron movement, the solid oxide electrolysis cell 300 can electrolyze water to form hydrogen at the fuel electrode 320 and oxygen at the air electrode 310.
[0105] A method of manufacturing a solid oxide cell according to another aspect includes: forming a fuel electrode; forming a solid oxide electrolyte on the fuel electrode; and forming an air electrode on the solid oxide electrolyte.
[0106] The fuel electrode is formed by coating the surface of nickel oxide (NiO) particles with a heterogeneous metal alloyable therewith, and casting a composition for forming a fuel electrode including the nickel oxide particles coated with the heterogeneous metal into, for example, a sheet shape, and then firing it.
[0107] Here, the heterogeneous metal is not particularly limited as long as it can be reduced and can form an alloy with nickel, but it is more desirable if it is a metal that can be more distributed in the surface area of the particles after alloying. For example, the heterogeneous metal may include tin (Sn), indium (In), bismuth (Bi), gallium (Ga), or a combination thereof.
[0108] The method of coating the surface of the nickel oxide particles with the heterogeneous metal alloyable therewith may be sputtering, atomic layer deposition (ALD), physical vapor deposition (PVD) or chemical vapor deposition (CVD).
[0109] For example, when tin (Sn) is coated on the surface of nickel oxide particles by sputtering, during the firing of the fuel electrode, the contraction of nickel (Ni) is delayed, so that nickel (Ni) is widely distributed without aggregation. Thus, the density of the three-phase boundary of the fuel electrode can be increased. In addition, at this time, tin (Sn) is reduced to form an alloy with nickel (Ni), but tin (Sn) is mainly distributed in the surface area of the alloy oxide particles. As a result, when the solid oxide battery is driven, the degradation caused by the aggregation of nickel can be prevented and the durability can be improved.
[0110] The composition for forming the fuel electrode may also include a solid oxide electrolyte material. Since the description of the solid oxide electrolyte material is the same as above, repeated description will be omitted. In addition, optionally, the composition for forming the fuel electrode may also include a dispersant, a plasticizer, a binder or a solvent, and may be in the form of a slurry, a paste or a dispersion.
[0111] The composition for forming a fuel electrode may be cast into a sheet shape using a wet method (eg, a dipping method, a coating method, a printing method, or a spraying method).
[0112] For example, firing may be performed in an air atmosphere at a temperature of 1000° C. to 1500° C. (e.g., 1300° C. to 1500° C. or 1400° C. to 1450° C.) However, the method of manufacturing a solid oxide cell according to this aspect is not limited thereto, and the fuel electrode may be fired together with the solid oxide electrolyte after forming the solid oxide electrolyte.
[0113] For example, the solid oxide electrolyte may be prepared by casting a composition for forming a solid oxide electrolyte into a sheet shape on a fuel electrode and then firing it.
[0114] The composition for forming a solid oxide electrolyte may include a solid oxide electrolyte material. Since the description of the solid oxide electrolyte material is the same as above, repeated description will be omitted. In addition, optionally, the composition for forming a solid oxide electrolyte may also include a dispersant, a plasticizer, a binder or a solvent, and may be in the form of a slurry, a paste or a dispersion.
[0115] The composition for forming a solid oxide electrolyte may be cast into a sheet shape using a wet method (eg, an impregnation method, a coating method, a printing method, or a spraying method).
[0116] For example, firing may be performed at a temperature of 1000° C. to 1500° C. (eg, 1300° C. to 1500° C. or 1400° C. to 1450° C.) in an air atmosphere.
[0117] The air electrode may be manufactured by using the composition for forming an air electrode, for example, by casting the composition for forming an air electrode into a sheet shape on a solid oxide electrolyte and then firing it.
[0118] The composition for forming the air electrode may include an air electrode material and a solid oxide electrolyte material. Since the description of the air electrode material and the solid oxide electrolyte material is the same as the air electrode material and the solid oxide electrolyte material described above, repeated description will be omitted. In addition, optionally, the composition for forming the air electrode may also include a dispersant, a plasticizer, a binder or a solvent, and may be in the form of a slurry, a paste or a dispersion.
[0119] The composition for forming an air electrode may be cast into a sheet shape on a solid oxide electrolyte by using a wet method (eg, an impregnation method, a coating method, a printing method, or a spraying method).
[0120] For example, firing may be performed at a temperature of 1000° C. to 1500° C. (eg, 1300° C. to 1500° C. or 1400° C. to 1450° C.) in an air atmosphere.
[0121] In the above, it is described that a solid oxide electrolyte is formed on a fuel electrode and an air electrode is sequentially formed on the solid oxide electrolyte, but the method for manufacturing a solid oxide cell according to the present aspect is not limited to this, but the fuel electrode, the air electrode and the solid oxide electrolyte may be formed separately and then stacked, or after forming a solid oxide electrolyte on the air electrode, the fuel electrode may be sequentially formed on the solid oxide electrolyte.
[0122] In addition, although firing is described as being performed after forming a fuel electrode, after forming a solid oxide electrolyte, and after forming an air electrode, respectively, the method for manufacturing a solid oxide cell according to the present aspect is not limited to this, but a solid oxide electrolyte may be formed on the fuel electrode and then firing may be performed simultaneously after forming an air electrode on the solid oxide electrolyte, or a solid oxide electrolyte may be formed on the fuel electrode and then fired together, and an air electrode may be formed thereon and then fired together.
[0123] Hereinafter, specific examples of the present invention are presented. However, the following examples are only intended to specifically illustrate or explain the present invention, and the scope of the present invention should not be limited thereto.
[0124] [Preparation Example: Fabrication of Solid Oxide Battery]
[0125] (Example 1)
[0126] 1) Fabrication of nickel oxide particles coated with heterogeneous metals (SnO2@NiO)
[0127] 0.1 g to 2 g of tin nitride based on 100 g of the nickel oxide particles was dissolved in water and sufficiently dispersed therein. Subsequently, the water was completely dried at 100° C. to prepare a powder.
[0128] When the electrode is made of this powder, SnO2 is formed on the NiO surface after firing, but the two metals Ni and Sn are reduced to metals and become alloys during the reduction process. When the alloy is formed, the Sn element is distributed more on the surface of Ni than inside Ni.
[0129] 2) Fabrication of solid oxide unit cells
[0130] 50 g of tin-coated nickel oxide particles (SnO2@NiO), 50 g of YSZ powder and 1.5 g of dispersant were added to 200 g of ethanol and then ball-milled for 24 hours. Then, 7 g of 10 wt% polyvinyl butyral ethanol solution and 40 g of binder solution (Kceracell Co., Ltd.) were added thereto and then ball-milled again for 24 hours to obtain a SnO2@NiO / YSZ dispersion.
[0131] Subsequently, the fuel electrode support with the film attached on the bottom surface was immersed in the SnO2@NiO / YSZ dispersion for 1 minute, and was lifted at a predetermined speed at room temperature and then dried for about 5 minutes. Here, a 10 μm thick SnO2@NiO / YSZ fuel electrode layer was formed on the upper surface of the fuel electrode support without the film attached.
[0132] 100g of YSZ powder and 1.2g of dispersant were added to 300g of ethanol, and then ball-milled for 24 hours. 11g of 10wt% polyvinyl butyral ethanol solution and 40g of binder solution (Kceracell Co., Ltd.) were added thereto, and then ball-milled again for 24 hours to obtain a YSZ dispersion. The fuel electrode support with a SnO2@NiO / YSZ fuel electrode layer attached was immersed in the YSZ dispersion for 2 seconds, lifted at a predetermined speed, dried at room temperature for about 5 minutes, and heat-treated by firing at 1300°C to form a 2μm thick YSZ electrolyte on the SnO2@NiO / YSZ fuel electrode layer.
[0133] 12g of YSZ powder and 12g of LSCF (La 0.6 Sr 0.4 Co 0.2 Fe 0.8 O3) powder is added to 12g of ethanol and then ball-milled for 24 hours. 4g of 10wt% polyvinyl butyral ethanol solution and 20g of binder solution (Kceracell Co., Ltd.) are added thereto, and then ball-milled again for 24 hours to obtain YSZ / LSCF slurry. The YSZ / LSCF slurry is screen-printed on the YSZ electrolyte layer of the fired half-cell and dried in an oven at 60°C for 3 hours to form a 15μm thick GDC / LSCF air electrode layer. Subsequently, the product is fired at 1050°C for 2 hours in a high-temperature furnace under an air atmosphere to complete the unit cell.
[0134] (Comparative Example 1)
[0135] A unit cell was manufactured in the same manner as in Example 1, except that nickel oxide particles (NiO) not coated with a heterogeneous metal were used instead of nickel oxide particles (SnO 2 @NiO) coated with a heterogeneous metal.
[0136] [Experimental Example 1: Analysis Results of Alloy Oxide Particles]
[0137] In the solid oxide cell of Example 1, EDS analysis was performed on the alloy oxide particles included in the fuel electrode, and the results were as follows: Figures 4 to 6 are shown in and summarized in Table 1.
[0138] Figure 4 is the HAADF phase of the alloy oxide particles, Figure 5 is the EDS mapping result of nickel (Ni), and Figure 6 is the EDS mapping result of tin (Sn). Figures 4 to 6 , frame 1 indicates the central region position of the alloy oxide particle, and frame 2 indicates the surface region position of the alloy oxide particle.
[0139] [Table 1]
[0140]
[0141] Reference Figures 4 to 6 As shown in Table 1, the at% of tin (Sn) in the surface region of the alloy oxide particle relative to all atoms is greater than the at% of tin (Sn) in the central region of the alloy oxide particle relative to all atoms, for example, the at% of tin (Sn) in the surface region of the alloy oxide particle relative to all atoms is about 19 times or more the at% of tin (Sn) in the central region of the alloy oxide particle relative to all atoms.
[0142] [Experimental Example 2: Performance Measurement of Solid Oxide Battery]
[0143] In the solid oxide cells of Example 1 and Comparative Example 1, scanning electron microscope (SEM) images (BED-C, 15.00 kV, WD, 10.1 mm, × 10.0 k) of the fuel electrodes are shown in FIG. Figure 7 and Figure 8 As shown in Figure 7 and Figure 8 In the figure, the bright part is YSZ, and the dark part is the alloy oxide particles or nickel oxide particles.
[0144] in addition, Fig. 9 Shows Figure 7 Alloy oxide particles and Figure 8 Respective size distribution of nickel oxide particles.
[0145] Reference Figures 7 to 9 , the solid oxide cell of Example 1 has a smaller particle distribution (average 500 nm) than the nickel oxide particle distribution of Comparative Example 1 (average 700 nm) due to delayed shrinkage during solidification.
[0146] In addition, the accelerated durability of the solid oxide cells of Example 1 and Comparative Example 1 with respect to carbon contamination was measured by injecting 100% of methane gas instead of hydrogen into the fuel electrode, and the results are as follows: Fig.10 as shown in .
[0147] Reference Fig.10 As a result of evaluating accelerated durability by supplying methane instead of hydrogen, the solid oxide cell of Comparative Example 1 did not last more than four and a half hours, but the solid oxide cell of Example 1 lasted for 6 hours or more, confirming high durability.
[0148] While the present invention has been described in conjunction with what are presently considered to be practical example embodiments, it is to be understood that the invention is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
[0149] <Description of Reference Numerals>
[0150] 100: Solid oxide battery
[0151] 110: Fuel electrode
[0152] 111: Alloy oxide particles
[0153] 112: Solid Oxide Electrolyte Materials
[0154] 120: Air electrode
[0155] 130: Solid Oxide Electrolyte
[0156] 200: Solid Oxide Fuel Cell
[0157] 210: Fuel electrode
[0158] 220: Air electrode
[0159] 230: Solid Oxide Electrolyte
[0160] 300: Solid Oxide Solid Oxide Electrolysis Cell
[0161] 310: Air electrode
[0162] 320: Fuel electrode
[0163] 330: Solid Oxide Electrolyte
[0164] 340: External power supply
[0165] Industrial Applicability
[0166] The present disclosure relates to a solid oxide battery and a method for manufacturing the same.
[0167] In accordance with a solid oxide cell according to one aspect, by delaying the shrinkage of nickel (Ni) during the firing of the fuel electrode, nickel (Ni) is widely distributed without aggregation, the density of the three-phase boundary is increased to improve performance, and by preventing degradation during operation of the fuel electrode, durability can be improved.
Claims
1. A solid oxide battery comprising: solid oxide electrolyte; and a fuel electrode and an air electrode, the fuel electrode being disposed on one side of the solid oxide electrolyte and the air electrode being disposed on the other side of the solid oxide electrolyte, The fuel electrode comprises alloy oxide particles of nickel (Ni) and a heterogeneous metal and a solid oxide electrolyte material, wherein the heterogeneous metal and nickel (Ni) can be alloyed, and 10×M core <M surface , where M core is the atomic percentage (at%) of the heterogeneous metal in the central region of the alloy oxide particle relative to all atoms, and M surface is the atomic percentage (at %) of the heterogeneous metal in the surface region of the alloy particle relative to all atoms.
2. The solid oxide battery according to claim 1, wherein: M core is the atomic percentage (at%) of the heterogeneous metal measured within the central region centered at the center of the alloy oxide particle and having a size of 10 nm×10 nm, and M surface is the atomic percentage (at %) of the heterogeneous metal measured within the surface region centered at an internal point within 20 nm toward the center from the surface of the alloy oxide particle and having a size of 2 nm×2 nm.
3. The solid oxide battery according to claim 1, wherein: In the central region of the alloy oxide particle, the heterogeneous metal is included in an amount of 0.01 at % or more and less than 1 at % based on the total number of atoms.
4. The solid oxide battery according to claim 1, wherein: In the surface region of the alloy oxide particle, the heterogeneous metal is included in an amount of 0.1 at % or more and less than 10 at % based on the total number of atoms.
5. The solid oxide battery according to claim 1, wherein: The heterogeneous metal includes tin (Sn), indium (In), bismuth (Bi), gallium (Ga), or a combination thereof.
6. The solid oxide battery according to claim 1, wherein: The solid oxide electrolyte material includes yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
7. The solid oxide battery according to claim 1, wherein: The solid oxide electrolyte includes yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
8. The solid oxide battery according to claim 1, wherein: The air electrode includes lanthanum strontium manganese oxide (LSM), lanthanum strontium iron oxide (LSF), lanthanum strontium cobalt oxide (LSC), lanthanum strontium cobalt iron oxide (LSCF), samarium strontium cobalt oxide (SSC), barium strontium cobalt iron oxide (BSCF), bismuth ruthenium oxide or a combination thereof.
9. The solid oxide battery according to claim 1, wherein: The solid oxide cell is a solid oxide fuel cell (SOFC), a solid oxide electrolyzer (SOEC), or both.
10. A method for manufacturing a solid oxide battery, comprising: coating the surface of nickel oxide (NiO) particles with a heterogeneous metal alloyable therewith; as well as A fuel electrode is formed using the composition for forming a fuel electrode including the nickel oxide particles coated with the heterogeneous metal.
11. The method according to claim 10, wherein: The heterogeneous metal is coated on the surface of the nickel oxide (NiO) particle using a sputtering method, an atomic layer deposition (ALD) method, a physical vapor deposition (PVD) method, or a chemical vapor deposition (CVD) method.
12. The method according to claim 10, wherein: The composition for forming the fuel electrode also includes a solid oxide electrolyte material.
13. The method according to claim 10, wherein: The step of forming the fuel electrode includes casting and firing the composition for forming the fuel electrode.
14. A solid oxide battery comprising: solid oxide electrolyte; and a fuel electrode and an air electrode, the fuel electrode being disposed on one side of the solid oxide electrolyte and the air electrode being disposed on the other side of the solid oxide electrolyte, The fuel electrode comprises a solid oxide electrolyte material and alloy oxide particles of nickel (Ni) and a heterogeneous metal, the heterogeneous metal and nickel (Ni) can be alloyed, the heterogeneous metal is mainly arranged in the surface region of the alloy oxide particles of nickel (Ni), and The heterogeneous metal includes tin (Sn), indium (In), bismuth (Bi), gallium (Ga), or a combination thereof.
15. The solid oxide battery according to claim 14, wherein: The surface region of the alloy oxide particle of nickel (Ni) is a region centered at an inner point within 20 nm from the surface of the alloy oxide particle of nickel (Ni) toward the center and having a size of 2 nm×2 nm.
16. The solid oxide battery according to claim 14, wherein: In the central region of the alloy oxide particle, the heterogeneous metal is included in an amount of 0.01 at % or more and less than 1 at % based on the total number of atoms, and The central region of the nickel (Ni) alloy oxide particle is a region centered at the center of the nickel (Ni) alloy oxide particle and having a size of 10 nm×10 nm.
17. The solid oxide battery according to claim 14, wherein: In the surface region of the alloy oxide particle, the heterogeneous metal is included in an amount of 0.1 at % or more and less than 10 at % based on the total number of atoms.
18. The solid oxide battery according to claim 14, wherein: The solid oxide electrolyte material includes yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
19. The solid oxide battery according to claim 14, wherein: The solid oxide electrolyte includes yttria-stabilized zirconia (YSZ), scandia-stabilized zirconia (ScSZ), gadolinia-doped ceria (GDC), samarium oxide-doped ceria (SDC), strontium and magnesium-doped lanthanum gallate (LSGM), barium zirconate doped with samarium oxide and ceria (BaZrO3), barium ceria doped with samarium oxide and ceria (BaCeO3), or a combination thereof.
20. The solid oxide battery according to claim 14, wherein: The atomic percentage of the heterogeneous metal relative to all atoms in the surface region of the alloy oxide particle is 19 times or more the atomic percentage of the heterogeneous metal relative to all atoms at the central region of the alloy oxide particle.
Citation Information
Patent Citations
Injection molding mold, injection stretch blow molding machine, and method for manufacturing hollow molded body
KR1020220159244A
Jig apparatus for vehicle parts assembly
KR1020230051468A